PELAKSANAAN PERKAWINAN SESUKU MASYARAKAT SUKU MELAYU BERDASARKAN HUKUM ADAT DI NAGARI PADANG SIBUSUK KECAMATAN KUPITAN KABUPATEN SIJUNJUNG - Annisa Desria Utami; Firdaus Firdaus; Hayatul Ismi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Minangkabau adheres to the matrilineal kinship system. Matrilineal kinship system is a kinship systemby drawing lineages based on maternal lines. Every offspring born from a marriage will enter his mother’sfamily. A marriage in minangkabau has a broad meaning. It is not just a meeting two peoples but morebroadly because it involves families of both parties. The marriage of the minangkabau community is exogamy.Exogamy which is done outside the tribe. It means that a person who wants to get married must find a partneroutside her/his tribe. The peoples who are married with some tribe called “tamakan pokok”. Minagkabaumarriage is regulated in a religious and customary manner.Some problem that will be discussed in this thesis namely: First, how to carry out the inter-teribalmarriage to melayu tribe community of Nagari Padang Sibusuk Kupitan Sub-District, Sijunjung Regency.Second, is the application of a marriage ban on intertribal marriage still maintained bt melayu tribecommunity of Nagari Padang Sibusuk, Kupitan Sub-District, Sijunjung Regency.the type of research is usesociological research, the form of the research is a law identification (unwritten law).The result of study can be concluded namely: First, the implementation of marriage between followmembers of the melayu tribe can occur as long as they come from different rumah gadang. Second, theprohibition on inter-tribal still runs in Nagari Padang Sibusuk, but in Melayu tribes it is possible to domarriage with fellow melayu tribes as long as they come from different rumah gadang. Of course, it will havean impact on the traditional order and the community life.Keywords : Marriage - Customary Law - Minangkabau